HOW CEO NARCISSISM SHAPES FIRM PERFORMANCE OVER TIME: EVIDENCE FROM INDONESIA - Meiliana Suparman; Tiffany Lim; Teddy Jurnali; Sheila Septiany; Iwan Suhardjo (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This study examined the impact of CEO narcissism and long-term firm performance in Indonesia. We utilized data from 2,618 observations of listed companies registered on the Indonesia Stock Exchange between 2017 and 2021, employing Ordinary Least Squares (OLS) regression analysis. The findings revealed a positive and significant impact of CEO narcissism on the current and future firm performance. These results are further validated through robust coarsened exact matching (CEM) tests. Furthermore, the study investigated the moderating effect of CEO tenure, revealing a weakening association between narcissism and performance over extended CEO leadership. In addition, CEO ownership and board size do not moderate this relationship. Our study offers valuable insights for Indonesian companies. While the study highlights a positive impact on performance, the moderating effect of CEO tenure suggests potential downsides to narcissism in the long run. This study offers valuable considerations on the impact of CEO narcissism and long-term firm performance in Indonesia. While narcissism appears beneficial for short- and medium-term performance, the moderating effect suggests potential long-term drawbacks that warrant further investigation.